The human olfactory receptor repertoire - Zozulya, Sergey (BioMed Central, 2001)
BACKGROUND: The mammalian olfactory apparatus is able to recognize and distinguish thousands of structurally diverse volatile chemicals. This chemosensory function is mediated by a very large family of seven-transmembrane olfactory (odorant) receptors encoded by approximately 1,000 genes, the majority of which are believed to be pseudogenes in humans. RESULTS: The strategy of our sequence database mining for full-length, functional candidate odorant receptor genes was based on the high overall sequence similarity and presence of a number of conserved sequence motifs in all known mammalian odorant receptors as well as the absence of introns in their coding sequences. We report here the identification and physical cloning of 347 putative human full-length odorant receptor genes. Comparative sequence analysis of the predicted gene products allowed us to identify and define a number of consensus sequence motifs and structural features of this vast family of receptors. A new nomenclature for human odorant receptors based on their chromosomal localization and phylogenetic analysis is proposed. We believe that these sequences represent the essentially complete repertoire of functional human odorant receptors. CONCLUSIONS: The identification and cloning of all functional human odorant receptor genes is an important initial step in understanding receptor-ligand specificity and combinatorial encoding of odorant stimuli in human olfaction.